Elixir or opiate?: an assessment of minor irrigation policies in North Bengal - Shah, Tushaar (International Water Management Institute, 2001)
Provides a socioeconomic analysis of Minor Irrigation (MI) investments in North Bengal. The study addresses the following questions: whether there is justification and rationale for MI subsidies in North Bengal; whether the North Bengal Terai Development Project's current subsidy policy achieves the Project's MI objectives in an efficient, sustainable and livelihood intensive manner, and if there is scope for modifying the current policies for better impact.